(untitled) (International Journal of Natural Sciences, 2012)
The study was conducted on live and slaughtered goats in Rajshahi district during the period of March, 2011 to February, 2012 by coproscopy and necroscopy studies respectively. The aim of this study was to determine the factors such as age, sex and breed of the goat which influences the prevalence of haemonchosis. The information was collected from farmers through a questionnaire. A total of 720 goats examined, of which 416 goats were found positive for Haemonchus infection and the overall prevalence of haemonchosis in goat was 57.8%. The prevalence rate was found to be higher in young (< 2 yrs), 63.8% compared to older (>2 yrs), 41.5% goats. It was observed that in relation to sex the prevalence of haemonchosis was higher in female, 63.9% compared to male, 50.0% goats. Among the breed, the crossbred goats were the maximum, 60.2% infection rate of haemonchosis than that of Black Bengal, 55.6% goats. The young stage and female goats are more prone to haemonchosis and statistically a significant difference (P<0.05) was noted but there is no significant difference (P>0.05) was found in breed of goats. The present study suggests that young aged and females goats were more susceptible but crossbred goats were slightly susceptible to haemonchosis and requires special attention for its control. International Journal of Natural Sciences (2012), 2(3):83-87 DOI: http://dx.doi.org/10.3329/ijns.v2i3.12137